Resolution of chiasmata in oocytes requires separase-mediated proteolysis. - Kudo, N; Wassmann, K; Anger, M; Schuh, M; Wirth, K; Xu, H; Helmhart, W; Kudo, H; McKay, M; Maro, B; Ellenberg, J; de Boer, P; et al. (2006)
In yeast, resolution of chiasmata in meiosis I requires proteolytic cleavage along chromosome arms of cohesin's Rec8 subunit by separase. Since activation of separase by the anaphase-promoting complex (APC/C) is supposedly not required for meiosis I in Xenopus oocytes, it has been suggested that animal cells might resolve chiasmata by a separase-independent mechanism related to the so-called "prophase pathway" that removes cohesin from chromosome arms during mitosis. By expressing Cre recombinase from a zona pellucida promoter, we have deleted a floxed allele of separase specifically in mouse oocytes. This prevents removal of Rec8 from chromosome arms and resolution of chiasmata. It also hinders extrusion of the first polar body (PBE) and causes female sterility. mRNA encoding wild-type but not catalytically inactive separase restores chiasma resolution. Both types of mRNA restore PBE. Proteolytic activity of separase is therefore essential for Rec8's removal from chromosome arms and for chiasma resolution but not for PBE.